2017
DOI: 10.1159/000468538
|View full text |Cite
|
Sign up to set email alerts
|

Skin Pigmentation Genetics for the Clinic

Abstract: Human pigmentation characteristics play an important role in the effects of sun exposure, skin cancer induction and disease outcomes. Several of the genes most important for this diversity are involved in the regulation and distribution of melanin pigmentation or enzymes involved in melanogenesis itself within the melanocyte cell present in the skin, hair and eyes. The single nucleotide polymorphisms and extended haplotypes within or surrounding these genes have been identified as risk factors for skin cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 110 publications
(170 reference statements)
1
70
0
1
Order By: Relevance
“…The three SNPs in the MTAP and PLA2G6 loci that were assayed as part of this study have been reported to be linked on extended haplotypes . The MTAP rs4636294*G melanoma protective allele was more common in the AHM group than the pigmented lesion group (53.4% vs. 41.7%; P = 0.02) whereas the PLA2G6 rs11570734*G protective allele was less common in the AHM group (23.9% vs. 36.6%; P = 0.02).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The three SNPs in the MTAP and PLA2G6 loci that were assayed as part of this study have been reported to be linked on extended haplotypes . The MTAP rs4636294*G melanoma protective allele was more common in the AHM group than the pigmented lesion group (53.4% vs. 41.7%; P = 0.02) whereas the PLA2G6 rs11570734*G protective allele was less common in the AHM group (23.9% vs. 36.6%; P = 0.02).…”
Section: Resultsmentioning
confidence: 86%
“…Tables and present the allelic and genotype frequencies of seven candidate genes with polymorphisms known to influence skin colour, naevi and melanoma . MC1R R alleles were more prevalent in AHM patients (51.1%) than the pigmented melanoma cohort (34.5%) or controls (22.3%; P = 0.002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be fascinating to explore if there is any association between natural loss‐of‐function variants of human MC1R and the efficacy of wound healing and extracellular matrix remodelling in men. Physiologically, hypomorphic variants of MC1R lead to reduced intracellular cAMP synthesis and are associated with the red hair pale skin phenotype in humans . In the context of wound healing, it is puzzling to note a recent a prospective cohort study of burned adult Black/African American and native American race that were independently associated with severe postburn hypertrophic scarring .…”
Section: Discussionmentioning
confidence: 99%